THE USE OF QUIZIZZ APPLICATION FOR MEASURING EFL STUDENTS’ ENGAGEMENT AT SD MUHAMMADIYAH MANYAR - Candra Hadi Asmara; Ribeh Najib Muhammad; Jihan Nawal Aini (IKIP Siliwangi, 2022)
Nowadays, learning through mobile phones is the best way to be applied during the teaching and learning process. The use of online applications to keep students engaged in the learning process is necessary since it will trigger their enthusiasm in obtaining knowledge of the target language. Quizizz is one online application that can be used as a learning tool. The method used in this research is quantitative research. The aim of this research is to measure the student’s engagement at SD Muhammadiyah Manyar Gresik using Quizizz application. The participants were 81 EFL students. They were given questionnaire about how they are engaged with Quizizz application during learning language activity. The result showed that the engagement score of Quizizz application is located at the highest Std. Deviation of the motivating criteria in question number 24 with a score of 1.155, and the highest mean score is in question number 20 with a score of 2.8148. Therefore, researchers concluded that Quizizz application can be the right media to enhance students’ engagement during the teaching and learning process. Keywords: Quizizz, Students’ Engagement, Teaching EFL